Lightweight concretes with fly–ash of Prydniprovsk thermal power station - Netesa, M. I.; Palanchuk, D. V.; Netesa, A. M. (Science and Transport Progress, 2013)
Purpose. Determination of conformities to law of influence of expense of components of easy concretes, which turn out on the basis of local afterproducts of industry, on their basic properties under conditions of enhanceable efficiency of the use of cement. Methodology. Experimental studies on optimization of structures and properties of concrete were carried out with use of mathematical planning experiments methods. All experiments were carried out on orthogonal design with three variables. Cement, water and additives PLKP-2 consumption were taken as varied factors. Findings. Vast experimental studies on determination of rational compositions of concrete mixtures were conducted with the use as fillers of granulated slag from iron and steel plant named after Petrovskiy and Dnepr sand, as binding agent Krivoy Rog portland-cement II/B-Ш-400, as filler fly-ash of Pridneprovsk Thermal Power Station. Efficiency coefficient of cement use was adopted as basic criterion of concrete composition rationality, it is determined on the relation of the attained durability per unit weight of used cement. For greater efficiency coefficient of cement use regularity of rational grain composition of components previously obtained was adopted, it is provided at a ratio of a large fraction consumption to medium and small 52:23:25, and their sizes are approximately 100:10:1. Experimental studies with use of mathematical planning experiments method were carried out. By results of their processing isofields were constructed according to the strength and effectiveness of the use of cement ratio of the studied factors. Originality. By strength comparative tests of hardened concrete with various local secondary resources, modified with complex plasticizer PLKP-2 additive, it was found that lightweight concrete with the density of 1700…1800 kg/m3 and concrete compressive strength from 5 to 20 MPa on the basis of granulated slag from the iron and steel plant named after Petrovskiy filled with fly-ash of Pridneprovsk Thermal Power Station during ensuring of rational grain composition of components with a ratio of major components of the fractions to medium and small 52:23:25 are the most effective. Practical value. Compositions of lightweight fine grained mixture based on granulated slag from the iron and steel plant named after Petrovskiy filled with fly-ash of Pridneprovsk Thermal Power Station and modified with complex plasticizer PLKP-2 additive were determined. They provide required concrete compressive strength within 5…10 MPa at a reduced cement consumption by approximately 20% as compared to the traditionally used compositions for these purposes.